2002
DOI: 10.1152/ajprenal.00123.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mouse TonEBP-NFAT5: expression in early development and alternative splicing

Abstract: Tonicity-responsive enhancer binding protein (TonEBP)- nuclear factor of activated T cell family 5 is a DNA binding protein that plays a key role in the response of cells to hypertonicity. However, TonEBP is expressed and active in tissues that are in an isotonic milieu. To explore the biological role of TonEBP, we cloned mouse TonEBP that shares 92% of amino acids with the human counterpart. TonEBP is expressed in embryonic stem cells and throughout the stages of fetal development. Immunohistochemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…Remarkably, the depletion of ddx5 and ddx17 did not affect the total NFAT5 mRNA level in any of the tested cell lines (Figure 4c). However, RT-PCR using primers in exons 3 and 6 that flank known alternative exons 4 and 5 (Dalski et al, 2002;Maouyo et al, 2002) revealed that ddx5/ ddx17 depletion in MDA-MB-231, HeLa and MCF-7 cells favored the shorter NFAT5 product that did not contain exons 4 and 5 (E3/E6, Figure 4d). This result was further supported after sequencing the PCR products (not shown) and by quantifying NFAT5 splicing variants by RT-Quantitative (q)PCR.…”
Section: Nfat5 Ddx17mentioning
confidence: 99%
“…Remarkably, the depletion of ddx5 and ddx17 did not affect the total NFAT5 mRNA level in any of the tested cell lines (Figure 4c). However, RT-PCR using primers in exons 3 and 6 that flank known alternative exons 4 and 5 (Dalski et al, 2002;Maouyo et al, 2002) revealed that ddx5/ ddx17 depletion in MDA-MB-231, HeLa and MCF-7 cells favored the shorter NFAT5 product that did not contain exons 4 and 5 (E3/E6, Figure 4d). This result was further supported after sequencing the PCR products (not shown) and by quantifying NFAT5 splicing variants by RT-Quantitative (q)PCR.…”
Section: Nfat5 Ddx17mentioning
confidence: 99%
“…First, NFAT5 RNA expression is not limited to the kidney, but is in fact ubiquitous (10,15,18). Analysis of protein expression further indicates that NFAT5 is expressed in essentially all tissues of the developing embryo, with particularly high levels of expression in the brain and heart (19). In adult tissues detectable NFAT5 protein is limited to the thymus and mitogen-activated primary T lymphocytes (15).…”
mentioning
confidence: 99%
“…NFAT5, the only known osmosensitive transcription factor, is expressed in many tissues bathed in either isotonic or hypertonic environment in vivo [12,15]. A genome database search reveals that Rel-like transcription factors are present in Drosophila and mammals but not in Caenorhabditis elegans, yeast, and plants [18].…”
Section: Discussionmentioning
confidence: 99%
“…NFAT5 is expressed not only in the renal medulla that is significantly hyperosmolar but also in the brain, thymus, liver, and many other tissues that are not in hypertonic milieu under physiological conditions [12,17]. However, its expression in hybridoma cells has not been reported before.…”
Section: Expression Of Nfat5 In Hybridoma Cells and Its Regulation Bymentioning
confidence: 99%
See 1 more Smart Citation